Hypothalamo-pituitary-adrenal axis activity and related factors in adolescent during a tennis tournament (Annals of Medical Research, 2021)
Aim: Adolescence is an important period of development and during this period young people are more susceptible to mental illnesses. Therefore, a comprehensive knowledge of the factors that mediate stress response can help developing our understanding of these diseases. The aim of this study is to examine the activity of hypothalamo–pituitary–adrenal axis and determine factors affecting this activity in adolescents. Material and Methods: The adolescents between the ages of 14 and 17, who participated in the official amateur tennis tournament, were included in the study. The data form, including questions for the assessment of the stress level and sociodemographic variables was filled. Then, salivary cortisol levels were measured before (-5 minutes) and after (+5 minutes) the first match of the official tennis tournament. Results: The mean salivary cortisol levels were 40.8±53.8 ng/ml, before the game and 98.8±150.5 ng/ml, after the game (p=0.008). The salivary cortisol levels were statistically higher, after the game, in males, those who won, and those who felt anxious compared the before. Conclusion: The results of this study showed that salivary cortisol level can be used in the assessment of stress response in adolescents and various factors such as gender, mood, and state of winning are effective on cortisol response.
Keywords: Adolescent; hypothalamo-pituitary-adrenal axis; salivary cortisol; stress; tennis; tournament